Internal Communication Management Strategy to Increase Office Administration Effectiveness - Agus Yulistiyono; Izlan Sentryo; Hady Siti Hadijah; Ita Musfirowati Hanika; Triatmi Sri Widyaningsih (Borong Newinera Publisher, 2024)
This research discusses Internal Communication Management Strategies to Increase the Effectiveness of Office Administration at PT Hana Kreasi Utama in Jakarta using a combined qualitative and quantitative approach. Using interview, observation and documentation study methods, this research aims to understand the impact of internal communication strategies on the effectiveness of office administration. Involving all PT Hana Kreasi Utama employees, this research obtained in-depth data and statistics to support the analysis. The research results show that the company implements internal communication strategies such as integrated systems, regular meetings, and technology. This strategy positively impacts interdepartmental efficiency and collaboration, speeds up workflow, and increases employee understanding of company goals. Discussion of the research results links the findings to organizational communication theory, highlighting the importance of factors such as message alignment and employee participation. Key factors supporting success involve message alignment, openness, and employee participation. These findings strengthen the relationship between effective internal communication and administrative performance. Practical implications and recommendations are presented to support companies in improving their internal communications management. Comparison with previous research confirms the consistency of the internal communication strategy findings. Nonetheless, contextual differences need to be taken into account, and the practical implications of previous research can help companies improve strategy implementation. This discussion provides a comprehensive understanding of the importance of Internal Communication Management Strategies to Increase the Effectiveness of Office Administration at PT Hana Kreasi Utama in Jakarta.